Ask a Question

Post a LessonAnswered on 19/11/2016 CBSE/Class 10/Mathematics Tuition/Class IX-X Tuition Ratio and Proportion

Richa Kumari

-1

Like 1

Answers 26 Comments Answered on 06/12/2016 CBSE/Class 10/Mathematics Tuition/Class IX-X Tuition Ratio and Proportion

Ankit D. Javeri

Mathematics Tutor

If a:b::c:d then ad= bc. Therefore, 0.75:x::5:8 implies 5x=8*0.75 i.e., x=6/5=1.20.

Like 1

Answers 12 Comments Answered on 27/11/2016 CBSE/Class 10/Mathematics Tuition/Class IX-X Tuition Ratio and Proportion

Shyam

Trainer

49/9 or 5.44

Like 0

Answers 14 Comments Answered on 05/12/2016 CBSE/Class 10/Mathematics Tuition/Class IX-X Tuition Ratio and Proportion

Chandan Singh

Tutor

Mean proportion = square root of (25*64) = 40 Ans.

Like 1

Answers 8 Comments Answered on 22/11/2016 CBSE/Class 10/Mathematics Tuition/Class IX-X Tuition Ratio and Proportion

RAM MOHAN A.

The answer is 5:1. SOL :- x : y=9 : 10==> 10 x=9 y==> 5 x = 9 y/2, substituting 9y/2 for 5x in ( 5 x + 3 y) : (5 x - 3 y) gives 5: 1

Like 0

Answers 10 Comments Answered on 25/11/2016 CBSE/Class 10/Mathematics Tuition/Class IX-X Tuition Ratio and Proportion

Nagesh Guledagudda

Programming Passionate

(B/C ) * (C/D)= (6/7) * (14/15) => B/D = 4/5 => (A/B)*(B/D)=(4/5)*(4/5) => A/D = 16/25.

Like 1

Answers 8 Comments Answered on 20 Mar CBSE/Class 10/Mathematics Tuition/Class IX-X Tuition Ratio and Proportion

Vikas Verma

Tutor

4 : 5.

Like 1

Answers 6 Comments Answered on 06/12/2016 CBSE/Class 10/Mathematics Tuition/Class IX-X Tuition Ratio and Proportion

Sarvajeet Kumar

An Experienced Trainer

(By Componendo and Dividendo) 8a:18b=8c:18d or a:b = c:d.

Like 0

Answers 3 Comments Answered on 08/12/2016 CBSE/Class 10/Mathematics Tuition/Class IX-X Tuition Ratio and Proportion

Rama Krishna Ravulapalli

Rs. 1,90,085.

Like 0

Answers 4 Comments Answered on 07/12/2016 CBSE/Class 10/Mathematics Tuition/Class IX-X Tuition Ratio and Proportion

If x : y : z, show that x : z = (square of x) : (square of y)?

Shambhavi S.

As we know that , x:y:z , this implies that, y^2=x*z. Simplifying x:z=x^2:y^2, we get, y^2=x*z, which is the same as above. Thus, they are equal.

Like 0

Answers 1 Comments UrbanPro.com helps you to connect with the best in India. Post Your Requirement today and get connected.

x

Ask a Question